Bake-partitioning in a press-hardening steel. (15th March 2019) - Hou, Z.R.; Opitz, T.; Xiong, X.C.; Zhao, X.M.; Yi, H.L.
Abstract: Bake-partitioning, a process integrating paint-baking of car-body assembling to induce carbon partitioning into austenite, has been proposed for enhancing the ductility of press-hardening steels. Carbon is estimated to diffuse a maximum distance of 2.7 nm in austenite at 170 °C for 20 min. Austenite films with a thickness of approximately 5 nm are therefore desired for sufficient bake-partitioning. This was realised by the ultra-fine prior austenite grain due to 7 wt% of manganese addition combined with vanadium carbide precipitation. The novel alloy exhibits 1800 MPa ultimate tensile strength combined with 16% elongation, which has never been achieved in press-hardening steels. Graphical abstract: Unlabelled Image